DNA metabarcoding for diet analysis and biodiversity: A case study using the endangered Australian sea lion (Neophoca cinerea). Issue 14 (12th June 2017) - Berry, Tina E.; Osterrieder, Sylvia K.; Murray, Dáithí C.; Coghlan, Megan L.; Richardson, Anthony J.; Grealy, Alicia K.; Stat, Michael; Bejder, Lars; Bunce, Michael
Abstract: The analysis of apex predator diet has the ability to deliver valuable insights into ecosystem health, and the potential impacts a predator might have on commercially relevant species. The Australian sea lion ( Neophoca cinerea ) is an endemic apex predator and one of the world's most endangered pinnipeds. Given that prey availability is vital to the survival of top predators, this study set out to understand what dietary information DNA metabarcoding could yield from 36 sea lion scats collected across 1, 500 km of its distribution in southwest Western Australia. A combination of PCR assays were designed to target a variety of potential sea lion prey, including mammals, fish, crustaceans, cephalopods, and birds. Over 1.2 million metabarcodes identified six classes from three phyla, together representing over 80 taxa. The results confirm that the Australian sea lion is a wide‐ranging opportunistic predator that consumes an array of mainly demersal fauna. Further, the important commercial species Sepioteuthis australis (southern calamari squid) and Panulirus cygnus (western rock lobster) were detected, but were present in <25% of samples. Some of the taxa identified, such as fish, sharks and rays, clarify previous knowledge of sea lion prey, and some, such as eel taxa and two gastropod species, represent new dietary insights. Even with modest sample sizes, a spatial analysis of taxa and operational taxonomic units found within the scat shows significant differences in diet between many of the sample locations and identifies the primary taxa that are driving this variance. This study provides new insights into the diet of this endangered predator and confirms the efficacy of DNA metabarcoding of scat as a noninvasive tool to more broadly define regional biodiversity. Abstract : The Australian sea lion is an endangered apex predator which is endemic to Western Australia. We collected and extracted the DNA from 36 scats taken from five known sea lion haul out locations around the southeast coast of Western Australia. Several assays were used to target barcode sequences to both identify the diet of the sea lions and gain insight into the biodiversity of their habitats.